Adjustment to multiple sclerosis and identity satisfaction among newly diagnosed women: what role does motherhood play?. Issue 3 (15th March 2020) - Graziano, Federica; Calandri, Emanuela; Borghi, Martina; Bonino, Silvia
ABSTRACT: The present study aimed to describe the levels of depressive symptoms, affective well-being and identity satisfaction in a group of women recently diagnosed with multiple sclerosis (MS), accounting for differences in age, motherhood, and disease duration. Moreover, the role of identity satisfaction in depressive symptoms and affective well-being was evaluated, examining the moderating effect of motherhood. The study involved 74 women, aged between 19 and 57 years ( Mean = 37.7 years, SD = 10.7 years). Thirty-two women (43.2%) had children, aged between 2 and 29 years. All women had relapsing-remitting multiple sclerosis (RRMS) and mild to moderate disability. Mothers experienced greater depressive symptoms than childless women. Moreover, motherhood moderated the effect of disease duration on adjustment, with mothers reporting greater depressive symptoms, less affective well-being and less identity satisfaction than childless women as time passed since the diagnosis. Finally, greater identity satisfaction was related to less depressive symptoms and greater affective well-being, with a moderating effect of motherhood. The results outline the relevance of the process of identity redefinition for women's adjustment to MS early in the illness. Moreover, the results underscore the need to take into account the additional burden of motherhood when promoting women's adjustment to MS.